PENERAPAN MODEL PEMBELAJARAN EXPERIENTIAL LEARNING (EL) UNTUK MENINGKATKAN KEMAMPUAN BERBICARA DAN PRESTASI BELAJAR - Sabaruddin (UNIB Press, 2022)
The purpose of this study is to describe the effectiveness of the application of the Experiential Learning model to increase the Speaking Ability and Student Achievement. This research has been carried out with an experimental model of classroom action research at SMP Negeri 6 Lahat. of English subjects in class VIII . The research method used was Classroom Action Research (CAR) and quasi-experiments. The subjects of this study were eighth grade students of SMP Neger 6 Lahat in the second semester of the 2020/2021 school year. The number of students for the PTK class was 20 people, for the experimental class there were 20 people, and for the control class there were 20 people. Data collection methods in this study used the observation sheet Experiential Learning model, Speaking observation sheet, and English outcomes test. Data analysis using analysis of average scores and tests consisting of different tests between cycles and different tests of two samples that are not related .From the results of the study show that the application of the Experiential Learning model can increase speaking English and outcomes in subjects in class VIII of SMP Negeri 6 Lahat. This research was conducted in three cycles to determine that the application of Experiential Learning improved students' speaking ability and student achievement results from the first cycle to the third cycle. This proves that the application of the Experiential Learning Model not only improves students' speaking ability but also increases understanding of the material and this has the impact of increasing student Student Achievement results. The technique of taking PTK by means of observation and tests, while the experimental class only tested the simulation learning model. Data analysis used the t-test. Based on the data analysis of this study, it was found that there were differences in the learning model that used Experiential Learning to increase Speaking Ability by 73% and student Student Achievement increased by 95% in English Learning.